Apatite-forming ability of sandblasted and acid-etched titanium surfaces modified by ultraviolet irradiation: An in vitro study. Issue 5 (May 2022) - Li, Shaobing; Lin, Jiating; Lin, Xi; Liu, Xiangning; Jia, Fang; Gao, Yan; Ni, Jia; Xu, Shulan; Shao, Longquan; Cao, Li
Introduction: Contamination of large grit sandblasting and acid-etching (SLA) with hydrocarbons make the surface hydrophobic and influence its bioactivity. Preservation in dH2 O (modified SLA, modSLA) and ultraviolet (UV) irradiation were proven to be effective in decreasing hydrocarbon contamination and keeping the SLA surface hydrophilic. Aims: The aim of this study was to detect the in vitro bioactivity of SLA, modSLA and UV-SLA surfaces. Design: The SBF model was used to compare the bone-like apatite forming ability. Setting: The experiment was conducted at Southern Medical University. Materials and methods: The quantity of apatite was assessed by SEM and weighed on an electronic balance. The elemental composition and crystal phase were assessed by EDS and XRD analysis, respectively. Results: The sediments that completely covered the modSLA and UV-SLA surfaces after 4 weeks of soaking reached 3.23 ± 0.35 mg and 2.13 ± 0.95 mg, respectively. They were eight- and five-fold than that on the SLA surface (0.43 ± 0.15 mg) with statistical significance ( p  < 0.05 and p  < 0.01, respectively). EDS and XRD tests recognized the sediments on the modSLA and UV-SLA surfaces as apatite with similar elemental compositions, Ca/P ratios and crystal phases. Discussion: Hydrophilicity and abundant hydroxyl groups drive modSLA and UV-SLA surfaces to absorb more Ca 2+ to accelerate the formation of apatite. Conclusion: SLA preservation in dH2 O and UV irradiation were recognized as trustworthy methods to acquire greater bioactivity of the SLA surface.